Reversible dysfunction of T-lymphocytes in common variable immunodeficiency. - Marshall, W. H. (1977)
A 30-year-old man with recurrent sinopulmonary infections, eventually fatal, was found to have common variable immunodeficiency. In addition to low serum immunoglobulin concentrations he also had lymphopenia and cell-mediated immunodeficiency as shown by cutaneous anergy and a poor lymphocyte response to phytohemagglutinin (PHA) in vitro. However, intradermal injection of PHA produced a vigorous cutaneous response, showing that some cell-mediated responsiveness remained. The responsiveness of his lymphocytes to PHA was restored towards normal (confirmed by chromosome studies) by the addition of a small number of normal leukocytes to cultures; thus a reversible functional defect in his T-lymphocytes was revealed. Experiments indicated that the defect was cellular and not due to serum factors and it was concluded that normal leukocytes restored a missing factor to the patient's T-lymphocytes. Although counts of macrophage precursor cells in the bloodstream were low, thus contributing to the immunodeficiency, this could not have caused the reduced PHA response. Several relatives of this patient had lymphoma; two cousins had common variable immunodeficiency.